Sterilizations during the Alberto Fujimori’s government: family planning policy or intentional crimes and crimes against humanity? - Montoya Vivanvo, Yván (IUS ET VERITAS, 2014)
Given the unresolved status of the cases of victims of forced sterilizations during the government of Alberto Fujimori, this report aims to identify criterias of rationality from criminal doctrine and jurisprudence developed over the years, that will enable judicial officers to get a fair decision, consistent with a Constitutional Democracy, when determining criminal responsibility.Also, with the review of Salomon Lerner and Yvan Montoya, renowned lawyers defenders of human rights and knowledgeable in the subject.